2016
DOI: 10.5123/s2176-62232016000500015
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and ecology of sand flies (Psychodidae: Phlebotominae): foci of cutaneous leishmaniasis in Amazon Region, Brazil

Abstract: The aim of this study was to describe the phlebotomine sand fly fauna and its respective ecological indexes in risk zones of cutaneous leishmaniasis (CL). The study was carried out in the Municipality of Santarém, Pará State, Brazil. From the total of 102 records of CL patients in 2010 and 2011, infected with different Leishmania species, 31 were selected. Kernel density analysis was performed. CDC light traps were placed (6 p.m.-6 a.m., three nights, height of 1.5 m) in the identified risk zones (indoors, chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
1
5
0
1
Order By: Relevance
“…In localities with such small temperature variation, changes in the rainfall and humidity should have a larger influence on the fluctuation of Lu . longipalpis population, as demonstrated by other authors’ findings [72, 73, 74, 80]. However, our findings did not found humidity influence, possibly because humidity also has a small range of variation in Camaçari as well as coastal area, humidity remains high during the whole year.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…In localities with such small temperature variation, changes in the rainfall and humidity should have a larger influence on the fluctuation of Lu . longipalpis population, as demonstrated by other authors’ findings [72, 73, 74, 80]. However, our findings did not found humidity influence, possibly because humidity also has a small range of variation in Camaçari as well as coastal area, humidity remains high during the whole year.…”
Section: Discussionsupporting
confidence: 62%
“…Several authors found a correlation with climatic factors, observing a higher prevalence of Lu . longipalpis during the rainy season [70, 71, 72, 73, 74], and other ones demonstrated a preference of this species to dry and rocky areas [75, 76, 77]. The lack of correlation among climatic factors and sand fly density in the beachfront area, where more than 96% of sand flies were captured, and the limited correlation found in central area indicated that other factors could be more important in modulating the sand fly population than climatic factors in the area studied.…”
Section: Discussionmentioning
confidence: 99%
“…anduzei and Ny. antunesi, were found in the intradomicile and peridomicile areas, which shows an alert because finding females of these species close to the dwellings indicates the search for sources for blood meal making the risk of cases of ATL increase drastically (Tanure et al, 2015;Gonçalves et al, 2016). Bi.…”
Section: Discussionmentioning
confidence: 91%
“…(V.) braziliensis in Acre (Ávila et al, 2018), Rondônia (Grimaldi et al, 1991) and Pará (Souza et al 2010), Le. (L.) amazonensis in Amazonas and Rondônia (Resadore et al, 2019), besides being also considered one of the potential vectors of Leishmania (V.) naiffi in the Amazon region (Castellón et al, 1994;Gontijo and Carvalho, 2003;Gonçalves et al, 2016). This species has already been found as the most abundant in studies carried out in the Eastern Amazon (18.2%) (Pereira Júnior et al, 2019), in our study, it was the fifth most collected species (6.0%), and was found infected with DNA from Leishmania spp.…”
Section: Discussionmentioning
confidence: 99%
“…O cenário epidemiológico da LVH encontrado nesse estudo está em consonância com outros trabalhos brasileiros que buscaram detectar e compreender o padrão de distribuição desse agravo, a exemplo da pesquisa realizada por Gonçalves et al (2016) que utilizaram a análise de Kernel e geoprocessamento de dados para avaliar a distribuição da LV no município de Santarém-PA, sendo possível evidenciar que as mudanças ambientais, as migrações e a adaptação dos flebotomíneos aos centros urbanos, mudaram o padrão de adoecimento da população. O mesmo também pôde ser visto em estudo realizado por Mendes et al (2016) em Belo Horizonte-MG.…”
Section: Discussionunclassified